Pengaruh Strategi Pernyataan Benar atau Salah melalui Google Form dalam Pengetahuan Awal Pemahaman Konsep Matematika - B.R.E Yunanda; Afriwes Afriwes (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2023)
The purpose of this study was to test students' initial understanding of mathematical concepts. The type of research conducted belongs to quasi-experimental research (quasi-experimental) and this research involves two classes, namely the experimental class which will receive treatment by applying the true or false statement learning model and the control class using conventional learning. The test results show that: (1) There are differences in the results of the conceptual understanding tests between students who are taught by learning strategies of true or false statements and conventional learning models. This difference indicates that the conceptual understanding of students who are taught with a true or false statement learning strategy is higher than the conceptual understanding of students who are taught conventionally. (2) There are differences in the results of conceptual understanding tests between students who are taught with true or false statements learning strategies and conventional learning models. This difference indicates that the conceptual understanding of students who have high prior knowledge who are taught with a true or false statement learning strategy is higher than the conceptual understanding of students who have high prior knowledge who are taught conventionally. (3) There are differences in the results of conceptual understanding tests between students who are taught by learning strategies of true or false statements and conventional learning models. This difference indicates that the conceptual understanding of students who have low prior knowledge who are taught with true or false statements learning strategies is higher than the conceptual understanding of students who have low prior knowledge who are taught conventionally. (4) There is no interaction between learning models and prior knowledge in influencing students' understanding of grade VIII SMPN 2 Koto Besar concepts.